AHRUF SAB’AH DAN QIRAAT SAB’AH - Suarni, Suarni (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
This study explains the difference between the meaning of ahruf sab'ah and qiraat sab'ah. These two terms are a discussion of the ulumul of the Qur'an. both terms have different meanings, but are interrelated. The discussion on the qiraat sab'ah can not be separated from the discussion of ahruf sab'ah. Because ahruf sab'ah is as a result of the emergence of sabah qiraat. But the term qiraat sab'ah appears not merely because of ahruf sab'ah, meaning the term Ahruf Sab'ah appears when the Qur'an is revealed to the Prophet Muhammad, while Qiraat sab'ah arises because of the emergence of various Imam readings Qurra in the recital of the Qur'an which is briefly the seven Imams.